Wormhole Detection using Topology Graph based Anomaly Detection (TOGBAD) - Gerhards-Padilla, Elmar; Aschenbruck, Nils; Martini, Peter (Electronic Communications of the EASST, 2011)
Routing Attacks are a serious threat to communication in tactical MANETs. TOGBAD is a centralised approach, using topology graphs to detect such attacks. In this paper, we present TOGBAD’s newly added wormhole detection capability. It is an adaptation of a wormhole detection method developed by Hu et al. This method is based on nodes’ positions. We adapted it to the specific properties of tactical environments. Furthermore, we present simulation results which show TOGBAD’s performance regarding the detection of wormhole attacks.